THE SOCIO-EDUCATIONAL FOUNDATIONS OF CREATING A NEW SPIRITUAL SPACE IN UZBEKISTAN - Mamatkulov Eldor Safarovich (Modern American Journals, 2025)
This article examines the socio-educational foundations of creating a new spiritual space in Uzbekistan. It explores the country’s ongoing reforms in the fields of education, culture, and social development, highlighting the role of national values, civic consciousness, and spiritual renewal in shaping modern society. The study discusses how educational institutions, community initiatives, and state policies contribute to strengthening moral culture, promoting enlightenment, and fostering a harmonious social environment. Special attention is given to the importance of spiritual heritage, youth education, and the formation of a value-based worldview that supports national development.
Keywords: Uzbekistan; spiritual space; enlightenment; socio-educational reforms; national values; moral culture; youth education; civic consciousness; social development.